Estigma social y la consolidacion afectiva en los adultos mayores del Centro de Salud Tipo C, Buena Fe, año 2019 - Cedeño Yepez, Mario (2019)
Social stigma is a very latent problem and difficult to counteract in our country, taking into account several ways to involve this social problem by implementing irrational ideas regarding older adults that cause them to directly trigger psychological problems towards people who They are responsible for them. It is necessary to implement an effective alternative to begin to reduce these types of inconveniences implemented by all these stereotypes formed by people who have all these wrong ideas regarding older adults, sensitizing and raising awareness of all their family members can reduce all these acts that do not allow the affective consolidation of them This report will show as a first instance all the psychological problems and also all the types and forms of stigmas that are evident in each moment of society from which they emit towards the elderly, a survey was conducted directed towards the elderly and their relatives who attend all the programs established by the Centro de Salud Tipo C – Buena fe, to verify the problem directly. In addition to having a proposal aimed at raising awareness for the reduction of social stigma in the emotional consolidation of older adults of the Centro de Salud Tipo C – Buena fe.